Capital Taxation May Survive in Open Economies - Michael Braulke; Giacomo Corneo (Center for Economic Studies and ifo Institute (CESifo), 2003)
When capital is perfectly mobile across countries and labour is fixed, a source-based tax on capital both reduces and redistributes world income. We show that under plausible circumstances there always exists a country that benefits from introducing such a tax.
Keywords: 330